Eurasian jays (Garrulus glandarius) conceal caches from onlookers - Legg, Edward W. (Springer Berlin Heidelberg, 2014)
Animals that cache food risk having their stored food pilfered by conspecifics. Previous research has shown that a number of food-caching species of corvid use strategies that decrease the probability of conspecifics pilfering their caches. In this experiment, we investigated whether Eurasian jays (Garrulus glandarius) would choose between caching behind an opaque and caching behind a transparent barrier whilst being observed by a conspecific. If caching in out-of-sight locations is a strategy to prevent conspecifics from pilfering these caches, then the jays should place a greater proportion of caches behind the opaque barrier when being observed than when caching in private. In accordance with this prediction, jays cached a greater proportion of food behind the opaque barrier when they were observed than when they cached in private. These results suggest that Eurasian jays may opt to cache in out-of-view locations to reduce the likelihood of conspecifics pilfering their caches. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10071-014-0743-2) contains supplementary material, which is available to authorized users.